Teaching Reading in the Social Studies - Ediger, Marlow ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1999)
Social Studies teachers need to emphasize reading instruction across the curriculum; they can consider 11 selected methods to assist pupil progress in reading social studies content. Recommendations include introducing new words from the reading; initiating peer reading and tutoring; having an aid read orally; tape recording the selection to be read; encouraging individualized reading; selecting relevant spelling words; and assigning related writing activities. The teacher needs to use these procedures which guide pupils to achieve as optimally as possible in reading. Ideas gleaned through reading should provide facts, concepts, and generalizations, necessary for creative and critical thinking as well as problem solving. (SC)
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Content Area Reading; Creative Thinking; Critical Thinking; Elementary Education; Peer Teaching; Problem Solving; Social Studies; Teaching Methods; Writing Assignments; Reading Across the Curriculum; Guides, Classroom -- Teacher